Photos of marine litter in the shallow seafloor of the southernmost North and Baltic seas during the Walther Herwig III cruise WH462 in 2022 - Nogueira, Pedro; Kammann, Ulrike; Aust, Marc-Oliver (PANGAEA, 2024)
The dataset is a set of photos of marine litter at the seafloor and corresponding coordinates. The photos were taken in the southernmost North and Baltic seas, between 30.11.2022 and 12.12.2022 during the Walther Herwig III 462 research cruise (Date begin: 29.11.2022 - Date end: 14.12.2022, harbor begin: Bremerhaven - harbor end: Bremerhaven) . The video system used consists of a GoPro HERO 9 black in an aluminium case mounted in the front of the sledge and two lights with a total of 7200 lumen. Three laser pointers mounted in an equilateral triangle (laser center point distance 25.5 cm) provided the size reference for the video observation. The photos were taken as part of a study to visually quantify the amount of marine letter in the seafloor and compare this value with bottom trawl data.
Keywords: litter at the seafloor; marine litter; photos